The Use of Problem Based Learning (PBL) Method in Teaching English Writing at SMAN 5 Makassar - Nurul Hidjrah Hairuddin (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2018)
The Use of Problem Based Learning (PBL) Method in Teaching English Writing at SMAN 5 Makassar. The aims of the research were to: (1) determine whether the use of the Problem Based Learning Method improves students’ writing skill, and (2) disclose the students’ perceptions regarding the implementation of the Problem Based Learning in teaching ‘Writing’. This research employed a quasi- experimental design. The subjects of the research were the eleventh grade students of natural science class selected by means of random sampling. The data were collected by utilizing two kinds of instruments, a test and questionnaire. The data were analyzed using SPSS version 20 and disclosed the frequency, mean score, normality test, and nonparametric test (Mann-Whitney U test and Wilcoxon test). The results of this research indicated that the use of the PBL method contributed to the students’ writing performance. The results of the Man-Whitney U test demonstrated a significant difference in terms of the mean score between experimental group treated using PBL method and controlled group without treatmet (14.44 > 10.25). In addition, Wilcoxon test showed between the two groups (14.4 : 9.95). The results confirmed that the implementation of PBL method contributed to the students’ improvement of writing skills.The improvement was concerned with five components of writing, such as content, organization, vocabulary, grammar, and mechanics. Meanwhile, analysis of perceptional questionnaire indicated that the experimental group had positive perception on the use of PBL method.